"Qaid" leader "Si Lakhdar" and his migration to the Levant in 1910 - dahmani, omar (Journal of Social Sciences and Humanities, 2025)
The oued chouly area is among the most important areas that witnessed the emergence of intellectual awareness and the crystallization of national identity among some personalities whose activities accompanied the course of the renaissance in Algeria. Those who sought to address all the arbitrary practices imposed on them by the French colonial administration on a large scale. Perhaps among the most prominent personalities who accompanied this activity in all its fields in oued chouly, we mention the leader "Si Lakhdar", who had a great and important role in defending the people of the region, since he assumed the position of "Qaid" on the throne of oued chouly, and thus he contributed greatly In the crystallization of national awareness among the people of the region. It is noted that this crystallization of the national consciousness, to which the leader "Si Lakhdar" contributed, greatly helped in continuing the struggle activities at the level of the throne of oued chouly, which was mainly represented in standing up to the French colonial policy that sought to obliterate the national identity and spread ignorance and superstition among the population